ANALISIS PENDAPATAN USAHATANI MINAPADI DI KABUPATEN SUKOHARJO - Lestari, Diyah Tri; Sumarjono, Djoko; Ekowati, Titik (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 13 No 3 (2019): Vol. 13, No. 3, 2019, 2019)
The demand of paddy commodity is high, so paddy productivity needs to be increased. One way to increase productivity is land diversification through minapadi. Sukoharjo Regency is one of the development sites of Minapadi. The transition from the paddy monoculture system to minapadi provides a change for farmers both from technical cultivation, inputs, costs and income. This research aims to analyze net income of minapadi and paddy monoculture, profitability of minapadi dan paddy monoculture, comparation between net income of minapadi and paddy monoculture, comparation between profitability of minapadi and paddy monoculture, and analyze comparation between profitability of minapadi with bank deposit rate. Research method is sencus with 33 repondents who applied minapadi and previoudly carried out paddy monoculture. The research was conducted in November-Desember 2018 in the Gatak and Tawangsari District, Sukoharjo Region. Data were collected by interview using quetionnaires. Data were analyzed by net income analyze and profitability analyze. Hypothesis testing by paired sample t test and one sample t test. The results showed that net income of minapadi (IDR 11,417,133/season/4,152 m 2 ) greater than net income of paddy monoculture (IDR 7,564,842/season/4,152 m 2 ), minapadi profitability (77.69%) and paddy monoculture profitability (142.86%) was a significant different. Profitability of minapadi is greater than bank deposit rate (5.5%).